HUBUNGAN KADAR FIBRINOGEN PLASMA DAN MIKROALBUMINURIA PADA PENDERITA DIABETES MELLITUS TIPE 2 - Rikarni .; lillah .; yoesri . (INDONESIAN JOURNAL OF CLINICAL PATHOLOGY AND MEDICAL LABORATORY, 2007)
Increase of fibrinogen concentration in type 2 diabetic patients is an indicator for vascular inflammation, endothelial dysfunction. Hyperfibrinogenemia is a strong marker and independently for atherosclerosis. Beside that, hyperfibrino -genemia can precede macroand microvascular complication. In type 2 diabetic, microalbuminuria is early marker for diabetic nephropathy and show that there isendothelial dysfunction. Microalbuminuria not only useful to predict renal damage, but also useful to predict cardiovascular damage.Microalbuminuria is a marker for endothelial dysfunction. To know the correlation between increase of fibrinogen concentration andmicroalbuminuria in type 2 diabetic patients. The study was performed in Dr. M. Djamil central Hospital by using cross sectionalmethod and consecutive random sampling. Sample were type 2 diabetic patients included criteria were measured albumin/ creatinineratio and the patients was divided in 2 group, that is group A (normoalbuminuria) and group B (microalbuminuria) with totalsample were 90 patients. Each group were performed measurement of albumin/ creatinine ratio, random glucose concentration, andfibrinogen concentration in plasma. In group A, we found the average of albumin/ creatinine ratio is 6.6 μg/mg and in group B is107.5 μg/mg. The average of random glucose concentration in group A is 181.3 mg/dl, and in group B is 204 mg/dl and the difference of concentration is not significantly (p > 0.05). The average of fibrinogen concentration in group A is 383.5 ± 104.6 mg/dl, and in group B is 467 ± 79 mg/dl. Increasing fibrinogen concentration in group B is higher than group A and the increasing is significantlystatistical difference (p <0.05). In this study we also founded the positive correlation between concentration of fibrinogen plasma andalbuminuria ( r = 0.036, p =0.0004). In type 2 diabetic patients with normoalbuminuria has been increased fibrinogen concentration,and the increasing of fibrinogen concentration in type 2 diabetic patients with microalbuminuria is higher than type 2 diabetic patientswith normoalbuminuria. There are positive correlation between fibrinogen plasma concentration and albumin/creatinine ratio